A Conceptual replication of the differential price framing effect in the field - Sören Köcher; Markus Husemann-Kopetzky; Marie Schirmbeck; Melina Hess; Fabian Gmeindl; Samuel Hess (Marketing Letters, 2023)
Across a series of 10 laboratory and online studies, Allard, Hardisty, and Griffin (2019) demonstrated an increased preference for premium, higher-priced products over standard products when consumers were presented with the additional cost of the higher-priced option (i.e., differential price framing; e.g., "for 20 more") rather than with its total price (i.e., inclusive price framing; e.g., "for 60 total"); a phenomenon referred to as the differential price framing effect. In this paper, we conceptually replicate this effect in a field experiment that focuses on the application of a differential price framing strategy to a specific product format; namely, multipacks of identical products. Consistent with the differential price framing effect, the present study shows—based on 45,626 add-to-cart events and 30,426 completed product purchases on an online retailer's website—that the choice shares of higher-priced options increase when a differential price framing strategy is used. However, compared to non-consequential add-to-cart activities, this bias is considerably less pronounced in actual purchase patterns.
Keywords: 380; Differential Price Framing; Conceptual Replication; Partitioned Pricing; Consumer Choice; Field Experiment